The Dialogue Among Religions: Looking Back, Looking Ahead - Heisig, James W. (Bulletin of the Nanzan Institute for Religion & Culture, 1993)
Since its inception, the Nanzan Institute has sponsored biannual symposia，bringing together leading scholars from Japan ys major religions for dialogue with Christian scholars of religion. The eighth such symposium was held in thefirst days of September, 1992，on the topic aThe Dialogue Among Religions: Looking Back, Looking Ahead. ” The papers and discussions are scheduled to be published in spring of 1993. The following is a translation of the opening address.